2020
DOI: 10.3390/ma13051029
|View full text |Cite
|
Sign up to set email alerts
|

Dental Implants with Different Neck Design: A Prospective Clinical Comparative Study with 2-Year Follow-Up

Abstract: The present study was conducted to investigate whether a different implant neck design could affect survival rate and peri-implant tissue health in a cohort of disease-free partially edentulous patients in the molar–premolar region. The investigation was conducted on 122 dental implants inserted in 97 patients divided into two groups: Group A (rough wide-neck implants) vs. Group B (rough reduced-neck implants). All patients were monitored through clinical and radiological checkups. Survival rate, probing depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 49 publications
1
19
2
Order By: Relevance
“…Moreover, the convergent crest module in short and ultra-short implants seems to have an important influence on marginal bone loss. Referring to biomechanical models which compare different crest modules, the quantity of bone present around the neck of the implant is fundamental for the distribution of the occlusal forces [ 62 , 63 ]. The transmission of vertical, horizontal and rotational forces on F-BIC is thus more favorable and homogeneous in implants with convergent crest module compared to implants with divergent crest module with the same diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the convergent crest module in short and ultra-short implants seems to have an important influence on marginal bone loss. Referring to biomechanical models which compare different crest modules, the quantity of bone present around the neck of the implant is fundamental for the distribution of the occlusal forces [ 62 , 63 ]. The transmission of vertical, horizontal and rotational forces on F-BIC is thus more favorable and homogeneous in implants with convergent crest module compared to implants with divergent crest module with the same diameter.…”
Section: Discussionmentioning
confidence: 99%
“…The Rhinoceros ® application (Robert McNeel & Associates, Seattle, USA) was used to measure bone loss, allowing us to scale the images and measure mesial and distal radiographic bone loss. Other authors have adopted the same method [ 8 , 13 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, a bone loss of <1.5 mm around the implant during the first year has been considered to be physiological. However, this figure needs to be redefined, since recent studies have found that bone loss is approximately between 0.8 ± 0.4 mm [ 6 , 7 ], and is dependent upon a range of factors such as the morphology and geometry of the implant, the surface of the implant neck, the technique used to place the implant, the patient habits, and the type of prosthesis [ 5 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review of this Special Issue summarizes the relevant literature to establish guidelines regarding the effects of connection type between abutments and implants in soft and hard tissues [ 6 ]. Biomechanical behaviours of implant-abutment connection designs are shown in two articles, and clinical outcomes are presented in one article, depending on the connection designs [ 7 , 8 , 9 ]. It is necessary for researchers and clinicians to interpret the clinical data in implantology in the light of the old axioms that pocket formation is the initiator for peri-implant or periodontal inflammation and that bone responds to strain, not to stress itself.…”
mentioning
confidence: 99%